Implementation of the FIRM (Foley Insertion, Removal, and Maintenance) protocol in skilled nursing facilities - Gokula, Murthy; Gaspar, Phyllis M (Translation: The University of Toledo Journal of Medical Sciences, 2014)
The purpose of this study was to determine the feasibility and outcomes of the implementation of an evidence based protocol, Foley Insertion Removal and Maintenance (FIRM) for the use and care management of indwelling urinary catheters (IUC) for skilled nursing facilities (SNF). The protocol consists of an order set for insertion, maintenance, and removal complemented with an education program for health care providers of SNF. It was implemented over a six month period in two SNF. Prospective chart review following implementation revealed an 11.3 rate of IUC per month. Documentation of the indication for placement of an IUC was 98.5%. Retrospective chart review revealed a lower use of IUC prior to implementation of the protocol but the lack of documentation of orders for IUC artificially reduced the rate. FIRM protocol is advocated as a facility policy with a nurse champion to facilitate implementation and surveillance.